Interactional effects of multidimensional perfectionism and cognitive emotion regulation strategies on eating disorder symptoms in female college students - TNG, Germaine Y. Q. (Institutional Knowledge at Singapore Management University, 2021)
Given the inconclusive findings regarding the relation between perfectionism and eating disorder symptoms, it is important that we determine whether this relation is modulated by emotion dysregulation, which is a prominent risk factor for eating disorders. We sought to identify specific cognitive emotion regulatory strategies—rumination, self-blame, and catastrophizing—that interact with multidimensional perfectionism to shape eating disorder symptoms (i.e., shape, weight, eating concerns, and dietary restraint). Using latent moderated structural equation modeling, we analyzed data from 167 healthy young female adults. We found that only rumination significantly moderated the relation between socially prescribed perfectionism and eating disorder symptoms. However, this was not observed for self-oriented perfectionism or other regulatory strategies. These findings held true when a host of covariates were controlled for. Our findings underscore the crucial role of rumination, a modifiable emotion regulatory strategy, in augmenting the relation between socially prescribed perfectionism and eating disorder symptoms in young women.